2013
DOI: 10.1136/bcr-2013-201229
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium phosphide-induced leukopenia

Abstract: SUMMARYAcute intoxication from the pesticide aluminium phosphide is a relatively rare, life-threatening condition in which cardiovascular decompensation is the most feared problem. We report the case of a patient exposed to aluminium phosphide-liberated phosphine gas. It resulted in the development of a gastroenteritis-like syndrome accompanied by severe reduction in white blood cell numbers as an early and prominent manifestation. By affecting important physiological processes such as mitochondrial function a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…In these cases, anxiety, excitation, cough, feeling of chest pressure, headache, dizziness, drowsiness, lethargy, anorexia, nausea, vomiting, dyspnea, retrosternal and epigastric pain was defined as symptoms in early period. Rarely, diarrhea can be observed in this period [14][15][16] . After affecting cardiovascular system, slimming pulse, arrhythmia, tachycardia, metabolic acidosis accompanied by hypotension, various ECG changes (such as ST elevation/depression, ORS and PR interval prolongation, complete heart block, fibrillation), treatment-resistant shock and peripheral circulatory disorders are some of clinical findings in aluminum phosphide intoxication 9,14 .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In these cases, anxiety, excitation, cough, feeling of chest pressure, headache, dizziness, drowsiness, lethargy, anorexia, nausea, vomiting, dyspnea, retrosternal and epigastric pain was defined as symptoms in early period. Rarely, diarrhea can be observed in this period [14][15][16] . After affecting cardiovascular system, slimming pulse, arrhythmia, tachycardia, metabolic acidosis accompanied by hypotension, various ECG changes (such as ST elevation/depression, ORS and PR interval prolongation, complete heart block, fibrillation), treatment-resistant shock and peripheral circulatory disorders are some of clinical findings in aluminum phosphide intoxication 9,14 .…”
Section: Discussionmentioning
confidence: 92%
“…During the aluminum phosphide intoxication, metabolic acidosis, mixed metabolic acidosis, respiratory alkalosis, acute renal failure and permanent and severe hypoglycemia may occur and they cause poor prognosis 15 . It was reported that there was leukopenia in cases following intoxication 16 . Also, increased cardiac stress can cause sudden cardiac deaths, and increased oxygen need and metabolic acidosis may worsen the clinical course…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In AF intoxication, the clinic findings are severe vomiting attacks, resistant hypertension, and metabolic acidosis. Through mitochondrial cytochrome C inhibition, it leads to cardiac and pulmonary toxicity [4,9]. Cardiac depression causes resistant hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Aluminium phosphide (AIP) is a highly toxic insecticide that widely used for preserving foods in the form of incense (1,2). AIP has been banned in some countries due to high toxicity and causing to death.…”
mentioning
confidence: 99%